IMPLEMENTASI SERTIFIKASI INDONESIAN SUSTAINABLE PALM OIL SYSTEM (ISPO) PADA PETANI KELAPA SAWIT SWADAYA DI KABUPATEN SANGGAU - Sabinus Sabinus; Erlinda Yurisinthae; Shenny Oktoriana (JSEP (Journal of Social and Agricultural Economics), 2021)
The increase in the number of smallholders (Independent farmers) in Bonti District faces challenges from limited knowledge about cultivation, optimizing the use of production factors, sustainability in production, and the absence of institutions (farmer groups, cooperatives, and farmer groups combined) so that it becomes a problem in the application of the 4 principles and 20 ISPO criteria. The purpose of this study is to analyze the formation of independent farmer groups within the ISPO certification framework. The research method uses the descriptive approach to analyze institutional conditions based on ISPO criteria also uses fishbone diagrams to find out the main problems and to create solutions. The results of this research show the farmers' institutional principles have not been implemented, while 65.96% of the ISPO criteria have not been implemented and only 34.04% of the ISPO criteria have been implemented by farmers. The absence of farmer groups, data collection, and counseling for independent farmer groups in Upe Village. However, farmers show a good response to the initiation of the farmer groups' formation because there is hope that it will facilitate production inputs and the sale of TBS.